Analysis of community‐level factors contributing to cholera infection and water testing access in the Northern Corridor of Haiti. (15th June 2021) - Ogisma, Lonege; Li, Tonghui; Xiao, Han; O'Donnell, Frances; Molnar, Joseph
Abstract: Vibrio cholera, the bacteria that cause cholera, is endemic in Haiti with a presence in both cities and remote areas. Improved access to drinking water testing and treatment in remote areas may reduce the impact of the disease. This case study uses correlation and regression analysis to identify the main factors that hinder access to water testing and that lead to high cholera infection rates among communities in the Northern Corridor of Haiti. Poor road conditions, mountainous terrain, and limited transportation options lead to high travel times up to 5.7 min/km between remote communities and drinking water testing facilities. The presence of springs in a community has a significant positive correlation with cholera infection rates in the Northern Corridor. However, socioeconomic factors had no significant correlation with cholera infection rate. The results of this study will be used to plan the implementation of a new drinking water testing laboratory near the city of Cap‐Haitian and other programs for vulnerable remote areas. Practitioner points: Topography and road conditions may be more important than distance in determining the accessibility of water testing facilities for rural communities. A lack of access to private vehicles is a substantial challenge for many rural communities in accessing water testing. The presence of springs in a community had a significant positive correlation with cholera infection rate. Abstract : Cholera is endemic in Haiti, and improved access to drinking water testing and treatment in remote areas may reduce the impact of the disease. This case study identifies the main factors that hinder access to water testing and may lead to high cholera infection rates in the Northern Corridor of Haiti. As shown, the average time required to transport samples to a drinking water laboratory varies substantially across the region and is related to factors other than distance. These values assume access to a private vehicle, and transit times on public transportation may be substantially longer.